Estudo morfológico comparativo das cascas e folhas de Stryphnodendron adstringens, S. polyphyllum e S. obovatum - Leguminosae - Sanches, Andréia C.C. [UNESP]; Lopes, Gisely C.; De Toledo, Cleyton E.M. [UNESP]; Do Sacramento, Luis V.S. [UNESP]; Sakuragui, Cássia M.; De Mello, João C. P. [UNESP] (My University, 2007)
The genus Stryphnodendron (S.) belongs to the family Leguminosae, subfamily Mimosoideae, which includes mostly trees of tropical and subtropical South America. Extracts of the stem bark are used traditionally by the local population to treat leucorrhoea and diarrhoea, as anti-inflammatory and antiseptic agents (antimicrobial) and to promote blood clotting and wound healing, and in a few cases of gastric ulcers. A review of the literature presented a previous morpho-anatomical study only for S. adstringens (Mart.) Coville. The aim of the present work is to compare morpho-anatomically the stem bark and leaves of three species of Stryphnodendron, known popularly as barbatimão: S. adstringens, S. polyphyllum and S. obovatum, in order to help botanical identification and contribute to quality control. Macro- and microscopical evaluation of the stem barks revealed no significant differences among the species. Morphological analyses of the leaves revealed differences in size, coloration, and pubescence. The leaves of S. adstringens are the largest, glabrous, and concolor. The leaves of S. polyphyllum are smaller, pubescent, and discolor; whereas the leaves of S. obovatum are the same size as those of S. polyphyllum, however, they are glabrous, and discolor.
Comparative morphological evaluation of stem bark and leaves of Stryphnodendron adstringens, s. polyphyllum and S. obovatum - Leguminosae
Keywords: Leaves; Macroscopic analyses; Microscopical analyses; Stem bark; Stryphnodendron adstringens; Stryphnodendron obovatum; Stryphnodendron polyphyllum; antiinfective agent; antiinflammatory agent; plant extract; Stryphnodendron adstringens extract; Stryphnodendron obovatum extract; Stryphnodendron polyphyllum extract; unclassified drug; bark; blood clotting; diarrhea; legume; leukorrhea; morphology; plant leaf; quality control; stomach ulcer; wound healing